Plantas hospederas de Bemisia tabaci (Homoptera: Aleyrodidae) en Cuba - Vázquez, Luis L (1996)
The sweetpotato whitefly, Bemisia tabaci, is an important pest of tomatoes and beans, among other crops, which transmits viral diseases. Since the second quarter of 1989 a significant population increase of this pest has been noled in severa! cultivated plants. From 1989 to 1992, a survey was done throughout the country, chiefly in vegetable and bean-producing areas. They occur in 119 species (42 families), a great increase over the previous record of four species. Wor1wide, this report represents 50 species and six families which are new records.